Challenges and Innovations in Public Sector Accounting: A Comparative Analysis - Papare, Endang Yokbet; Suratini, Suratini; Pasolo, Fahrudin (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2024)
This study aims to explore the influence of social accounting practices on community trust, focusing on the roles of transparency, stakeholder engagement, cultural context, regulatory frameworks, and media coverage. Utilizing a qualitative case study approach, the research involved in-depth analysis of various organizations to understand how their social accounting practices impact community trust. Data were collected through semi-structured interviews, focus groups, and document analysis and were then analyzed using thematic and content analysis techniques. The findings highlight that transparent social accounting practices are fundamental to building community trust. Detailed and honest disclosures about social and environmental impacts enhance organizational reliability and credibility. Stakeholder engagement emerged as critical, with participatory approaches fostering a sense of ownership and trust among community members. Cultural context significantly influences how communities perceive transparency and accountability efforts. The study also underscores the importance of regulatory frameworks and proactive media engagement in shaping public perceptions. The results align with previous research while providing a nuanced view of the interplay between these factors. This research contributes to academic knowledge and practical application, offering insights into how organizations can effectively implement social accounting practices to foster community trust. The originality lies in its comprehensive approach, considering multiple dimensions and contextual factors. The findings can guide policymakers, business leaders, and CSR practitioners in developing strategies that enhance transparency and accountability. Future research should consider quantitative approaches and longitudinal studies to validate and expand upon these findings.